2008
DOI: 10.1080/09500340701749943
|View full text |Cite
|
Sign up to set email alerts
|

Modeling optical transmission spectra of periodic narrow slit arrays in thick metal films and their correlation with those of individual slits

Abstract: We investigated the optical transmission of periodic narrow slit arrays in thick metal films with finite-difference time-domain simulations. Transmission spectra of ideal slit arrays of various structure parameters (film thickness, period, slit width) were calculated, and compared to those of single slits with the same width in metal films of the same thickness. It is observed that the transmission of individual slits are determinative to the transmission pass-bands of the slit arrays; while the arrayed slit s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…For small variations of the effective index, the N can be taken as the effective index of SP waves at the MDA surface N MDA eff À Á before modification, i.e., N % N MDA eff . It is also noted that, under normal incidence condition, the 2nd-order Bloch-mode is the lowest order mode (at the center of its reduced Brillouin zone) that can be excited by the grating at phase matching conditions with the 1st-order grating vector (i.e., b ¼ 1Â 2p=p) [20]. From the field distributions in Fig.…”
Section: Model Analysismentioning
confidence: 97%
“…For small variations of the effective index, the N can be taken as the effective index of SP waves at the MDA surface N MDA eff À Á before modification, i.e., N % N MDA eff . It is also noted that, under normal incidence condition, the 2nd-order Bloch-mode is the lowest order mode (at the center of its reduced Brillouin zone) that can be excited by the grating at phase matching conditions with the 1st-order grating vector (i.e., b ¼ 1Â 2p=p) [20]. From the field distributions in Fig.…”
Section: Model Analysismentioning
confidence: 97%
“…Due to excitation of bound surface plasmons (SP) in the ultra-thin metal layer of gratings [13][14][15], some anomalous optical properties arise. For example, it is well-known that an ultra-thin metal film without apertures allows considerable transmission of light, but it is recently disclosed by us and others that an apertured ultra-thin metal grating has strongly suppressed (or nearly null) transmission at some particular wavelength [1][2][3][4][5], which is later experimentally demonstrated [6,7]; this is in contrast to the enhanced optical transmission (EOT) through thick metallic subwavelength gratings [16][17][18][19]. In our previous study [4], the phenomenon is found to be related to in-plane resonance of the excited anti-symmetric bound SPs at the ridges of ultra-thin metal gratings, which results in anti-phase distributions of the field at the ridges and slits of the gratings on the transmission side.…”
Section: Introductionmentioning
confidence: 92%
“…Note that the field distribution at l= 620 nm is nearly the same as that at l=610 nm shown in k It should also be considered that the above in-plane SP modes in neighboring ridge regions of the gratings can also be laterally coupled. When phase matching conditions are satisfied for mode coupling [19], such interactions may lead to Bloch-wave resonances in x-direction, like resonances of SP/optical waves in a one-dimensional photonic crystal composed of air (in the slit region) and media with effective index of the SP modes (in the ridge region). For such subwavelength gratings, usually only the first-order phase matching condition is satisfied for normal incidence, which corresponds to second-order Bloch-wave resonance at the center of first Brillouin Zone [19].…”
Section: Analysis Of Plasmon Resonance Modes and Their Effects On Tramentioning
confidence: 99%
See 1 more Smart Citation
“…In the structure, the SMG acting as interdigitated electrodes has a lower capacitance than p-i-n structure, thus it can gain higher cutoff frequency. In addition, the subwavelength structure can provide extraordinary light transmission, which has been proved during the past years [3][4][5][6][7]. The present common understanding of the mechanism responsible for the extraordinary enhanced transmission is the excitation of horizontal surface plasmons (HSP) at the surface of the SMG.…”
Section: Introductionmentioning
confidence: 98%